1999
DOI: 10.1177/000313489906500610
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Experience with Hepatic Colorectal Metastasis

Abstract: The outcome of 134 patients undergoing hepatic resection for colorectal metastasis was studied. Current follow-up was available in 98 per cent of patients, for more than 5 years in 58 patients, and totaling 360 patient-years. Patients (52% male) had an average age of 62 ± 1 years (standard error of the mean). Time lapse between the primary colon surgery and hepatic resection was a median of 16 months and a mean of 19 ± 1 months. Thirty-two (24%) were operated on within 6 months for both their primary tumor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Surgical treatment for liver metastases from colorectal cancer is safe and potentially curative, with a 5-year survival rate of 25% to 40% [1][2][3]. After resection, however, it is estimated that the disease recurs in 60% to 85% of the patients; and in approximately 40% of these cases, the disease recurs in the form of isolated liver metastases [7][8][9][10]. The predictive factors for recur-rence following first resection of liver metastases have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment for liver metastases from colorectal cancer is safe and potentially curative, with a 5-year survival rate of 25% to 40% [1][2][3]. After resection, however, it is estimated that the disease recurs in 60% to 85% of the patients; and in approximately 40% of these cases, the disease recurs in the form of isolated liver metastases [7][8][9][10]. The predictive factors for recur-rence following first resection of liver metastases have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…these data suggest a possible correlation between metastasis and drug resistance mediated by P-gp [117]. an in vivo study conducted by Bradley et al [118] showed that different stages of tumor progression displayed different levels of P-gp m-rNa expression. Surprisingly, 460 lung metastases were examined and each metastasis was positive for P-gp.…”
Section: Relationship Between Drug Resistance and Invasionmentioning
confidence: 99%
“…Surgical resection is the most effective treatment for colorectal cancer that has metastasized to the liver. This treatment is widely accepted and has produced 5-year survival rates of 25-58 % [6][7][8][9][10]. Lung metastases were previously thought to be incurable and were treated primarily with systemic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%